2022
DOI: 10.1002/advs.202203665
|View full text |Cite
|
Sign up to set email alerts
|

Deconstruction of Vermal Cerebellum in Ramp Locomotion in Mice

Abstract: The cerebellum is involved in encoding balance, posture, speed, and gravity during locomotion. However, most studies are carried out on flat surfaces, and little is known about cerebellar activity during free ambulation on slopes. Here, it has been imaged the neuronal activity of cerebellar molecular interneurons (MLIs) and Purkinje cells (PCs) using a miniaturized microscope while a mouse is walking on a slope. It has been found that the neuronal activity of vermal MLIs specifically enhanced during uphill and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…Engagement in locomotion on the runged treadmill elicits a significant increase in MLI activity (Fig. 4H) similar to what has been reported for walking on flat surfaces (Jelitai et al, 2016;Ozden et al, 2012) or walking on a slope (Lyu et al, 2022). In line with the fact that cerebellar control of movement is predominantly ipsilateral (Darmohray et al, 2019;Heffley et al, 2018;Lee et al, 2015), we found that most cells in the left simplex were tuned to ipsilateral front left paw events, also the hind left paw events were more often observed than hind right events (Figs.…”
Section: Discussionsupporting
confidence: 87%
“…Engagement in locomotion on the runged treadmill elicits a significant increase in MLI activity (Fig. 4H) similar to what has been reported for walking on flat surfaces (Jelitai et al, 2016;Ozden et al, 2012) or walking on a slope (Lyu et al, 2022). In line with the fact that cerebellar control of movement is predominantly ipsilateral (Darmohray et al, 2019;Heffley et al, 2018;Lee et al, 2015), we found that most cells in the left simplex were tuned to ipsilateral front left paw events, also the hind left paw events were more often observed than hind right events (Figs.…”
Section: Discussionsupporting
confidence: 87%